Novel Ultrasound Image Acquisition Protocol and Scoring System for the Pediatric Knee. Issue 7 (12th June 2019) - Ting, Tracy V.; Vega‐Fernandez, Patricia; Oberle, Edward J.; De Ranieri, Deirdre; Bukulmez, Hulya; Lin, Clara; Moser, David; Barrowman, Nicholas J.; Zhao, Yongdong; Benham, Heather M.; Tasan, Laura; Thatayatikom, Akaluck; et al.
Abstract : Objective: The use of musculoskeletal ultrasound is increasing among pediatric rheumatologists. Reliable scoring systems are needed for the objective assessment of synovitis. The aims of this study were to create a standardized and reproducible image acquisition protocol for B‐mode and Doppler ultrasound of the pediatric knee, and to develop a standardized scoring system and determine its reliability for pediatric knee synovitis. Methods: Six pediatric rheumatologists developed a set of standard views for knee assessment in children with juvenile arthritis. Subsequently, a comprehensive literature review, practical exercises, and a consensus process were performed. A scoring system for both B‐mode and Doppler was then developed and assessed for reliability. Interreader reliability or agreement among a total of 16 raters was determined using 2‐way single‐score intraclass correlation coefficient (ICC) analysis. Results: Twenty‐one views to assess knee arthritis were initially identified. Following completion of practical exercises and subsequent consensus processes, 3 views in both B‐mode and Doppler were selected: suprapatellar longitudinal and medial/lateral parapatellar transverse views. Several rounds of scoring and modifications resulted in a final ICC of suprapatellar view B‐mode 0.89 (95% confidence interval [95% CI] 0.86–0.92) and Doppler 0.55 (95% CI 0.41–0.69), medial parapatellar view B‐mode 0.76 (95% CI 0.68–0.83) and Doppler 0.75 (95% CI 0.66–0.83), and lateral parapatellar view B‐mode 0.82 (95% CI 0.75–0.88) and Doppler 0.76 (95% CI 0.66–0.84). Conclusion: A novel B‐mode and Doppler image acquisition and scoring system for assessing synovitis in the pediatric knee was successfully developed through practical exercises and a consensus process. Study results demonstrate overall good‐to‐excellent reliability.